(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the place of studying keywords that form the core of Kyrgyz ethno culture in modern Kyrgyz linguistics. The directions for studying the word have been determined, and several materials in the Kyrgyz language confirm a comprehensive analysis of it from a new perspective.